2017
DOI: 10.20319/pijss.2017.32.16931706
|View full text |Cite
|
Sign up to set email alerts
|

The English Terms Used in Hotels and Tourism Places and Their Correspondences in Indonesian

Abstract: The research motivation is to find out proper Indonesian terms used for hotel and tourism facilities, and the objectives are to find out the correspondences of the English terms used in hotels and tourism places in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, one of the differences from other research is that this research stresses how the subjects of this research, both international and domestic hotel guests, comprehend the terms used at the hotel for amenities, services, and facilities. It should be emphasized that the differences between the prior research (see Rahayu, 2017) and this research are in the subjects and the hotels, as the research loci remain the same, but this research excluded tourist destinations. Similar research findings have been found on the strategies employed by the hotel guests who served as the study's subjects.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…However, one of the differences from other research is that this research stresses how the subjects of this research, both international and domestic hotel guests, comprehend the terms used at the hotel for amenities, services, and facilities. It should be emphasized that the differences between the prior research (see Rahayu, 2017) and this research are in the subjects and the hotels, as the research loci remain the same, but this research excluded tourist destinations. Similar research findings have been found on the strategies employed by the hotel guests who served as the study's subjects.…”
Section: Discussionmentioning
confidence: 98%
“…The results of this research on English hotel terms are consistent with the previous research (No Title, p.4 n.d.-b. ;Rahayu, 2017) and consistent use of terminology (see MacDonald et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations